2020
DOI: 10.4194/1303-2712-v20_7_01
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Effect of Origanum Extracts on the Gene Expression Profiles of Multidrug-resistant Isolates of Pseudomonas aeruginosa Retrieved from Oreochromis niloticus

Abstract: Pseudomoniasis has become a serious threat not only as a disease but also for the ensuing emergence of antibiotic-resistant bacteria. Thus, a total of 180 Oreochromis niloticus and water samples were collected from three intensive farms located in Ismailia Governorate for physicochemical and biological analysis. All retrieved isolates were tested for the presence of the P. aeruginosa oprL gene and for their sensitivity to commercial antimicrobial agents. Isolates showing multidrug resistance (MDR) were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…These active compounds can directly damage the cell membrane of Gram-positive bacteria, causing cell wall leakage, blocking enzyme systems and disruption of ion exchange (Burt, 2004;Holley & Patel, 2005). Moreover, carvacrol offers good antibacterial activity against various pathogenic bacteria by reducing virulence-related gene expression, impermeability and depolarization of the cytoplasmic membrane (Mabrok & Wahdan, 2018;Magi et al, 2015;Wahdan et al, 2020). In this study, there was a negative correlation coefficient between OEO concentrations and bacterial growth, which is in agreement with Popova and Bankova (2016) who reported that oregano oil showed a higher inhibitory effect on E. faecalis when given at low concen- (Tezel & Pavlostathis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These active compounds can directly damage the cell membrane of Gram-positive bacteria, causing cell wall leakage, blocking enzyme systems and disruption of ion exchange (Burt, 2004;Holley & Patel, 2005). Moreover, carvacrol offers good antibacterial activity against various pathogenic bacteria by reducing virulence-related gene expression, impermeability and depolarization of the cytoplasmic membrane (Mabrok & Wahdan, 2018;Magi et al, 2015;Wahdan et al, 2020). In this study, there was a negative correlation coefficient between OEO concentrations and bacterial growth, which is in agreement with Popova and Bankova (2016) who reported that oregano oil showed a higher inhibitory effect on E. faecalis when given at low concen- (Tezel & Pavlostathis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…P. aeruginosa rarely causes infections in healthy individuals, but it is a major threat to patients with malignancies or HIV infection, patients who are mechanically ventilated, patients, and individuals who are immunocompromised (Sadikot et al, 2015). P. aeruginosa generates an amazing array for both cell-associated and extracellular virulence factor to facilitate the establishment of infection (Wahdan et al, 2020). Numerous molecular methods to determine species level of Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%